Diagnosis, prognosis, and clinical management of mild traumatic brain injury - Levin, Harvey S; Diaz-Arrastia, Ramon R (Lancet neurology, 2015)
Concussion and mild traumatic brain injury (TBI) are interchangeable terms to describe a common disorder with substantial effects on public health. Advances in brain imaging, non-imaging biomarkers, and neuropathology during the past 15 years have required researchers, clinicians, and policy makers to revise their views about mild TBI as a fully reversible insult that can be repeated without consequences. These advances have led to guidelines on management of mild TBI in civilians, military personnel, and athletes, but their widespread dissemination to clinical management in emergency departments and community-based health care is still needed. The absence of unity on the definition of mild TBI, the scarcity of prospective data concerning the long-term effects of repeated mild TBI and subconcussive impacts, and the need to further develop evidence-based interventions to mitigate the long-term sequelae are areas for future research that will improve outcomes, reduce morbidity and costs, and alleviate delayed consequences that have only recently come to light.